Indications for surgical decompression in severe cerebral infarction - Ogashiwa, Motohide; Hara, Mitsuhiro; Tamagawa, Teruaki; Takeuchi, Kazuo; Shiogai, Toshiyuki (Japanese Journal of Stroke, 1981)
It is known that mortality and morbidity during the acute phase of a stroke are related to transtentorial herniation resulting from severe brain edema. The importance of transtentorial herniation with ischemic brain edema has been cverlookea in cerebral infarction, and no appropriate management for its prevention has been devised. Two cases demonstrating severe brain edema due to acute cerebral infarction resulting from occlusion of the unilateral internal carotid artery were presented, and both patients underwent decompressive surgery and one survived. We reviewed the literature and discussed indications for surgical decompression. Among reported 32 patients 17 died following the operation (mortality rate 53%). 16 patients were underwent surgical decompression within 2 weeks, whose preoperative neurological findings were stupor or coma in 16, 11 presented pupillary abnomality, 5 showed decerebrated or decorticate posturing, and 4 presented respiratory disturbance, Computerized tomography scans were useful in diagnosing cerebral infarction with transtentorial herniation. The clinical course, neurological signs and CT findings facilitated determination of indications for decompressive surgery. The signs and symptoms showing impending herniation were useful indicator of the timing of its surgery. If there has been irreversible damage to the brain stem, surgery will not result in any benefit. These findings are deep coma, dilated and fixed pupils, midline fixed eye position, and negative oculovestibular and corneal reflexies. Further medical and surgical management are required in such situation, and therefore neurological and neurosurgical intensive care is recommeded.